In vitro and in vivo comparison of three MR measurement methods for calculating Vascular shear stress in the internal carotid artery - MASARYK, A. M; FRAYNE, R; UNAL, O; KRUPINSKI, E; STROTHER, C. M (American journal of neuroradiology : AJNR, 1999)
Vascular abnormalities, such as atherosclerosis and the growth and rupture of cerebral aneurysms, result from a derangement in tissue metabolism and injury that are, in part, regulated by hemodynamic stress. The purpose of this study was to establish the feasibility and accuracy of determining wall shear rate in the internal carotid artery from phase-contrast MR data. Three algorithms were used to generate shear rate estimates from both ungated and cardiac-gated 2D phase-contrast data. These algorithms were linear extrapolation (LE), linear estimation with correction for wall position (LE*), and quadratic extrapolation (QE). In vitro experiments were conducted by using a phantom under conditions of both nonpulsatile and pulsatile flow. The findings from five healthy volunteers were also studied. MR imaging-derived shear rates were compared with values calculated by solving the fluid flow equations. Findings of in vitro constant-flow experiments indicated that at one or two excitations, QE has the advantage of good accuracy and low variance. Results of in vitro pulsatile flow experiments showed that neither LE* nor QE differed significantly from the predicted value of wall shear stress, despite errors of 17% and 22%, respectively. In vivo data showed that QE did not differ significantly from the predicted value, whereas LE and LE* did. The percentages of errors for QE, LE, and LE* in vivo measurements were 98.5%, 28.5%, and 36.1%, respectively. The average residual of QE was low because the residuals were both above and below baseline whereas, on average, LE* tended to be a more biased overestimator of the shear rate in volunteers. The average and peak wall shear force in five volunteers was approximately 8.10 dyne/cm2 and 13.2 dyne/cm2, respectively. Our findings show that LE consistently underestimates the shear rate. Although LE* and QE may be used to estimate shear rate, errors of up to 36% should be expected because of variance above and below the true value for individual measurements.